Massive decline of the world's largest king penguin colony at Ile aux Cochons, Crozet. Issue 4 (25th July 2018) - Weimerskirch, Henri; Le Bouard, Fabrice; Ryan, Peter G.; Bost, C.A.
Abstract: King penguins ( Aptenodytes patagonicus Miller) are major consumers in the Southern Ocean. The colony at Ile aux Cochons, Iles Crozet, in the southern Indian Ocean was known in the 1980s as the largest king penguin colony and the second largest penguin colony in the world. However, there have not been any recent estimates of this colony. Aerial photographs taken from a helicopter, and satellite images were used to report on changes in the colony and population sizes over the past 50 years. The colony has declined by 88% over the past 35 years, from c. 500 000 pairs to 60 000 pairs. The possible causes of this decline were explored but no plausible explanation for such an unprecedented decrease in penguin populations was found. The study highlights the use of satellite imagery as a non-invasive technique for population monitoring, and stresses the need for further research on the causes of this alarming trend in this colony.